Analysis of Factors Influencing Interest and Behavior in Using the Telegram Application: Implementation of the UTAUT 2 Model - Aryani, Reni; Cantika, Fiktor Fifi; Noverina, Yolla; Lestari, Dewi (Yayasan Gema Bina Nusantara, 2024)
The advancement of technology has transformed the global communication paradigm, particularly in Indonesia, where text-based communication has become a norm. Despite the superior security features and social elements of the Telegram instant messaging application, its popularity falls short of expectations. This research addresses this knowledge gap by employing the UTAUT2 approach, a model focused on individual technology acceptance introduced in 2013. Through quantitative data analysis and online questionnaires, the study engages Telegram users, employing purposive sampling with a minimum usage criterion of 3 months. Out of 160 processed questionnaires using PLS-SEM, only 4 hypotheses proved significant. The results reveal that effort expectancy, hedonic motivation, and user habit have a positive and significant impact on users' interest and usage behavior of the application. Conversely, variables such as performance expectancy, social influence, facilitating conditions, and price value do not have a significant impact. These findings offer crucial insights for the development of more effective applications aligned with user needs and contribute to understanding the factors influencing the adoption of instant messaging technology, particularly in the context of the Telegram application, in the evolving era of digital communication.